Kontribusi Supervisi Kepala Sekolah Model Pengembangan terhadap Profesionalisme Guru Sekolah Menengah Atas Negeri Provinsi Banten - Eneng Muslihah (Jurnal Pendidikan dan Kebudayaan, 2014)
This research undertaken at Banten province, aimed at 1) describing the level of the principal supervision of development model and teachers professionalism at public senior secondary schools, and 2) analyzing the contribution of the principal supervision of development model to the teachers professionalism at public senior high schools. The research method used was a quantitative correlation, with a sample of 200 teachers. For the development supervision model and professionalism of teachers a questionnaire was used as the instrument. The research results showed 1) a high level and satisfactory for the principal upervision of development model and the teachers professionalism, and 2) a positive and significant contribution of the principal supervision of development model to the teachers professionalism. Henceforth, the implementation of the rincipal supervision of development model constitutes one of the factors to determine the level of teachers’ the professionalism. ABSTRAK Penelitian yang dilakukan di propinsi Banten bertujuan 1) mendeskripsikan tingkat supervisi kepala sekolah model pengembangan dan profesionalisme guru dan 2) menganalisis kontribusi supervisi kepala sekolah model pengembangan terhadap profesionalisme guru Sekolah Menengah Atas Negeri. Metode penelitian yang digunakan yaitu kuantitatif korelasional, sedangkan sebagai sampel penelitian adalah 200 orang guru, dengan instrumen penelitian menggunakan angket. Hasil penelitian menunjukkan bahwa 1) tingkat supervisi kepala sekolah model pengembangan dan profesionalisme guru adalah tinggi dan memuaskan, dan 2)supervisi kepala sekolah model pengembangan berkontribusi terhadap profesionalisme guru. Dengan demikian, pelaksanaan supervisi kepala sekolah model pengembangan menjadi faktor yang dapat menentukan tinggi rendahnya profesionalisme guru.